Designable 3D Microshapes Fabricated at the Intersection of Structured Flow and Optical Fields. Issue 50 (21st October 2018) - Yuan, Rodger; Nagarajan, Maxwell B.; Lee, Jaemyon; Voldman, Joel; Doyle, Patrick S.; Fink, Yoel
Abstract: 3D structures with complex geometric features at the microscale, such as microparticles and microfibers, have promising applications in biomedical engineering, self‐assembly, and photonics. Fabrication of complex 3D microshapes at scale poses a unique challenge; high‐resolution methods such as two‐photon‐polymerization have print speeds too low for high‐throughput production, while top‐down approaches for bulk processing using microfabricated template molds have limited control of microstructure geometries over multiple axes. Here, a method for microshape fabrication is presented that combines a thermally drawn transparent fiber template with a masked UV‐photopolymerization approach to enable biaxial control of microshape fabrication. Using this approach, high‐resolution production of complex microshapes not producible using alternative methods is demonstrated, such as octahedrons, dreidels, and axially asymmetric fibers, at throughputs as high as 825 structures/minute. Finally, the fiber template is functionalized with conductive electrodes to enable hierarchical subparticle localization using dielectrophoretic forces. Abstract : A microshape fabrication method is presented that combines a thermally drawn transparent fiber template with a masked UV‐photopolymerization approach to enable biaxial control of a microshape design. High‐resolution production of complex microshapes not producible using alternative methods is demonstrated, such as octahedrons, dreidels, and axially asymmetric fibers, at throughputs as high as 825 structures min −1 .